84 SELF-MONITORING OF BLOOD GLUCOSE IN TYPE 2 DIABETES MELLITUS: USE OF AN AUTOMATED SELF-MANAGEMENT SYSTEM. (1st March 2007) - Oden, K. D.; Bomzer, T.; Knudson, P.; Fleming, R.; Levine, J.; Burns, E.; Flax, S.
Abstract : Purpose: Type 2 diabetes mellitus (T2DM) requires that a patient assume volitional control of a biologic process that is normally regulated automatically in the healthy individual (ie, serum glucose). Regular self-monitoring of blood glucose (SMBG) provides an objective feedback measure of glycemic control and a way to assess the effectiveness of self-management behaviors (medication dosing, diet, exercise). Patients must be shifted away from invalid, subjective cues to objective readings as indicators of disease control to maintain a valid behavioral control system. For older adults with T2DM, the high prevalence of cognitive impairment, depression, and other chronic illnesses that cause somatic symptoms makes this process even more challenging. We report the results of a clinical trial of an automated self-management system (ASMM) intended to assist in patient-centered management of T2DM by reminding older diabetic individuals to focus on SMBG as the primary indicator of glycemic control. Methods: The study was a randomized trial with "delayed intervention controls, " with half of participants randomized to immediate use of the ASMM and half to a delayed group, which continued usual care for 6 months before and then using an ASMM. The ASMM provided audio reminders to perform SMBG and take medication and user-friendly feedback about the pattern of glycemic control on a "real-time" basis. Participants were recruited from low-income senior housing and retirement communities in Milwaukee. Home visits were made every 3 months to measure HbA1c and collect other study measures. Results: Forty-four diabetic men and women completed the 12-month trial. Sixty percent were Caucasian, 32% African American, and 8% Hispanic, and the mean age was 70 years. Mean baseline A1c was 8.1% ± 1.0, and baseline cognition was 85 ± 2.5 on the 3MSE-R. A1c dropped to 7.3 ± 1.0 by 9 months ( F = 3.56, p < .004), with a 3-month lag observed in the DG. There was no relationship between 3MSE-R, depression scores, or A1c . Conclusion: Our results indicate that providing older diabetic individuals with audio reminders and feedback led to significant improvement in glycemic control over a 12-month trial period. This effect was independent of baseline cognitive status and mood.